Aspergillus sydowii: Genome Analysis and Characterization of Two Heterologous Expressed, Non-redundant Xylanases - Brandt, Sophie C.; Ellinger, Bernhard; van Nguyen, Thuat; Harder, Sönke; Schlüter, Hartmut; Hahnke, Richard L.; Rühl, Martin; Schäfer, Wilhelm; Gand, Martin (Frontiers in Microbiology, 2020)
A prerequisite for the transition towards a biobased economy is the identification and development of efficient enzymes for the usage of renewable resources as raw material. Therefore, different xylanolytic enzymes are important for efficient enzymatic hydrolysis of xylan-heteropolymers. A powerful tool to overcome the limited enzymatic toolbox lies in exhausting the potential of unexplored habitats. By screening a Vietnamese fungal culture collection of 295 undiscovered fungal isolates, 12 highly active xylan degraders were identified. One of the best xylanase producing strains proved to be an Aspergillus sydowii strain from shrimp shell (Fsh102) showing a specific activity of 0.6 U/mg. Illumina dye sequencing was used to identify our Fsh102 strain and determine differences to the Aspergillus sydowii CBS 593.65 reference strain. With activity based in-gel zymography and subsequent mass spectrometric identification three potential proteins responsible for xylan degradation were identified. Two of these proteins were cloned from the cDNA and, furthermore, expressed heterologously in E. coli and characterized. Both xylanases, were entirely different from each other, including glycoside hydrolases (GH) families, folds, substrate specificity and inhibition patterns. The specific enzyme activity applying 0.1% birch xylan of both purified enzymes were determined with 181.1 ± 37.8 or 121.5 ± 10.9 U/mg for xylanase I and xylanase II, respectively. Xylanase I belongs to the GH11 family, while xylanase II is member of the GH10 family. Both enzymes showed typical endo-xylanase activity, the main products of xylanase I are xylobiose, xylotriose and xylohexose, while xylobiose, xylotriose and xylopentose are formed by xylanase II. Additionally, xylanase II showed remarkable activity toward xylotriose. Xylanase I is stable when stored up to 30 °C and pH value of 9, while xylanase II started to lose significant activity stored at pH 9 after exceeding three days of storage. Xylanase II displayed about 40% activity when stored at 50 °C for 24 h. The enzymes are tolerant toward mesophilic temperatures, while acting in a broad pH range. With site directed mutagenesis, the active site residues in both enzymes were confirmed. The presented activity and stability justifies the classification of both xylanases as highly interesting for further development.